Manajemen Program Inovasi Pembiasaan Kemampuan Sosial Emosional Anak Usia Dini di RA An Nur Plus Jetis Mojokerto - Rumaiyah Rumaiyah; Mujiono Mujiono (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Based on the research results, it was found that: 1) The implementation of the SRA program policy at MAN 1 Gresik takes place in a Bottom Up manner based on the principles of child-friendly schools, namely non-discrimination, the best interests of children, non-violence, and respect for children by integrating several existing programs such as adiwiyata school programs, population alert schools (SSK), safe schools, inclusive schools, BPOM school snacks, UKS, Gerakan Ayo Membangun Madrasah (GERRAM). 2) Implementation of child-friendly school management begins with the planning stage and analysis of the situation and conditions, organizing and forming a team according to ability, implementing the principal's program as a role model, and evaluation is carried out directly and indirectly for 3 months once and once a year is done programmatically. 3) The implications of the SRA program are very positive for all school community members, the school environment, so that character, communication, and cooperation are well formed so that it becomes an educational institution categorized as BARIISAN (clean, safe, friendly, beautiful, inclusive, healthy, beautiful and comfortable) The creation of positive discipline which is the development of discipline and has a lot of achievements both academically and non-academically, the proof is that 105 out of 382 class XII students in 2023 have been accepted at PTN through the SBMPTN route, MAN 1 Gresik also won the title as the 2nd place in the Population Alert School at the East Java level.